Glycerol increases the yield and activity of human phenylalanine hydroxylase mutant enzymes produced in a prokaryotic expression system - Leandro, P (2015)
Chemical chaperones are low molecular weight compounds known to stabilize proteins in vitro. Recently it was shown that, in transfected cells, these molecules can also correct the defective folding of some mutant proteins. Hyperphenylalaninemia (HPA) has